2022
DOI: 10.1111/neup.12852
|View full text |Cite
|
Sign up to set email alerts
|

The receptor for advanced glycation end products and its ligands’ expression in OVE26 diabetic sciatic nerve during the development of length‐dependent neuropathy

Abstract: Type 1 diabetes (T1D) may affect the peripheral nervous system and alter the expression of proteins contributing to inflammation and cellular cytoskeleton dysfunction, in most cases leading to the development of diabetic length‐dependent neuropathy (DLDN). In the present study, we performed immunohistochemistry (IHC) to probe the expression of the receptor for advanced glycation end products (RAGE); its key ligands, high‐mobility group box 1 (HMGB1), S100 calcium‐binding protein B (S100B), and carboxymethyl‐ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
(230 reference statements)
0
3
0
Order By: Relevance
“…Our earliest studies revealed a decreased number of myelinated axons in diabetic models (Jaroslawska et al, 2021; Juranek, Geddis, Roasario, & Schmidt, 2013). However, the expression of beta actin did not differ in sciatic nerve harvested from diabetic and control group (Jaroslawska et al, 2021; Zglejc‐Waszak et al, 2022).…”
Section: Rage/diaph1 Crosstalk In Cytoskeleton Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our earliest studies revealed a decreased number of myelinated axons in diabetic models (Jaroslawska et al, 2021; Juranek, Geddis, Roasario, & Schmidt, 2013). However, the expression of beta actin did not differ in sciatic nerve harvested from diabetic and control group (Jaroslawska et al, 2021; Zglejc‐Waszak et al, 2022).…”
Section: Rage/diaph1 Crosstalk In Cytoskeleton Dynamicsmentioning
confidence: 99%
“…In silico analysis revealed that in diabetic sciatic nerve the most enriched biological pathway was that one related to the regulation of actin cytoskeleton (mmu04810, Zglejc‐Waszak et al, 2022). This phenomenon may suggest that actin cytoskeleton may play an essential role in therapeutic strategy to prevent perturbations in diabetic peripheral nerves.…”
Section: Rage/diaph1 Crosstalk In Cytoskeleton Dynamicsmentioning
confidence: 99%
“…We can speculate that the deletion of RAGE in ALS mice may inhibit progression of astroglia activation and gliosis during disease [32]. Moreover, we can hypothesize that the deletion of RAGE in ALS mice may inhibit progression of neurodegeneration and motor neuron damage (Fig 6) [7,15,23,32,37]. However, pathological mechanism of ALS is still not well known and poorly understood [1,6,21,22,35,36,26,[38][39][40][41].…”
Section: Plos Onementioning
confidence: 99%